Cranial Nerves and Plexuses Optic Nerve (N.II) - Rizqi, Amanda Suana; Sugiyanto, Aqilla Nasywa Nabila; Febianisa, Tabitha Afifah; Zulkifli, Yasmin Sabrina; Paradiesta, Andi Frieskha Naurah; Azzahra, Anis Aura; Rofilah, Alita Khainur; Sugiono, Muhammad Rafly Adrian; Fauzan, Naufal Revaldy; Haikal, Muhammad; Rifki, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cranial nerves are an integral part of the peripheral nervous system, playing a crucial role in transmitting afferent and efferent nerve impulses, particularly in the head and neck area. Unlike spinal nerves, cranial nerves have distinct functional nuclei in the brainstem, grouped into sensory (posterior and lateral) and motor (anterior) nuclei. The optic nerve is a purely afferent (sensory) nerve, responsible for transmitting visual information from rod and cone receptors in the retina to the lateral geniculate nucleus (LGN) and superior colliculus (SC) in the thalamus. The optic nerve's innervation pathway begins with retinal ganglion cells, which form nerve fibers, pass through the optic canal, and then cross at the optic chiasm. Disruption of this pathway can lead to various clinical manifestations, such as vision loss or visual field impairment, which will be discussed further. Therefore, a thorough understanding of the anatomy and function of the optic nerve is crucial for the diagnosis and treatment of neuro-ophthalmological conditions.